Early pharmacological inhibition of angiotensin-I converting enzyme activity induces obesity in adulthood - de Picoli Souza, Kely; da Silva, Elton D.; Batista, Elice C.; Reis, Felipe C. G.; Silva, Sylvia M. A.; Castro, Charlles H. M.; Luz, Jaqueline; Pesquero, Jorge L.; dos Santos, Edson L.; Pesquero, João B. (Frontiers in Pharmacology, 2015)
We have investigated early programming of body mass in order to understand the multifactorial etiology of obesity. Considering that the renin-angiotensin system is expressed and functional in the white adipose tissue (WAT) and modulates its development, we reasoned whether early transitory inhibition of angiotensin-I converting enzyme activity after birth could modify late body mass development. Therefore, newborn Wistar rats were treated with enalapril (10 mg/kg of body mass) or saline, starting at the first day of life until the age of 16 days. Between days 90th and 180th, a group of these animals received high fat diet (HFD). Molecular, biochemical, histological and physiological data were collected. Enalapril treated animals presented hyperphagia, overweight and increased serum level of triglycerides, total cholesterol and leptin, in adult life. Body composition analyses revealed higher fat mass with increased adipocyte size in these animals. Molecular analyses revealed that enalapril treatment increases neuropeptide Y (NPY) and cocaine- and amphetamine-regulated transcript (CART) gene expression in hypothalamus, fatty acid synthase (FAS) and hormone-sensitive lipase (HSL) gene expression in retroperitoneal WAT and decreases peroxixome proliferators-activated receptor (PPAR) γ, PPARα, uncoupling protein (UCP) 2 and UCP3 gene expression in WAT. The results of the current study indicate that enalapril administration during early postnatal development increases body mass, adiposity and serum lipids in adulthood associated with enhanced food intake and decreased metabolic activity in WAT, predisposing to obesity in adulthood.